Gambaran Tingkat Pengetahuan dan Praktik Siswi Boarding School Mengenai Higiene Menstruasi Area Urban di Yogyakarta - Dewi Fatma Mutiawati; Widyawati Widyawati; Wenny Artanty Nisman (PSIK FKKMK UGM, 2017)
Background: The density of students’ activities in boarding school needs to get care, especially in the practice of personal hygiene during menstruation. Menstruation process can lead to germs infection on the genital area which may cause diseases to the reproductive tract. To prevent this problem, it is important to do proper menstrual hygiene.Objectives: To identify the account of a boarding school student girls’ level of knowledge and practice of Menstrual Hygiene in an urban area of Yogyakarta.Method: This study was a quantitative descriptive using cross-sectional approach. The research was conducted in February 2017. The population of the research was female students’ boarding school in an urban area of Yogyakarta; where 124 female students were recruited for samples. Questionnaire was used as the data collection technique. Statistic descriptive technique was used for data analysis.Results: In general, respondents’ knowledge and practice of menstrual hygiene were good. Almost all respondents (98%) answered correctly on menstruation statements as normal and statements with many incorrect answers were menstruation as a sign of puberty. The practice of menstrual hygiene is most often done by respondents bathing more than once a day during menstruation (99,2%). As for the practice of menstrual hygiene which is still not quite right, namely the direction of cleaning the pubic area (45,2%).Conclusion: Respondents have accurate knowledge about menstrual hygiene. School manager (counseling and knowledge department) can increase the inappropriate menstrual knowledge and hygiene practice regarding to: hormones that affect menstruation, menstrual period, the frequency of replacement of the pads, the selection of material for disposing the pads and choosing right places to dry the underwear. ABSTAKLatar belakang: Padatnya aktivitas siswi di boarding school perlu mendapat perhatian terutama dalam penerapan kebersihan diri saat menstruasi. Proses menstruasi dapat mengakibatkan area genetalia rentan terinfeksi kuman sehingga menimbulkan penyakit saluran reproduksi. Untuk mencegah terjadinya permasalahan pada organ reproduksi maka perlu memperhatikan higiene menstruasi.Tujuan: Mengetahui gambaran tingkat pengetahuan dan praktik pada siswi boarding schoolmengenai higiene menstruasi area urban di Yogyakarta.Metode: Jenis penelitian ini adalah kuantitatif deskriptif dengan pendekatan cross sectional. Penelitian dilaksanakan pada Februari 2017. Populasi penelitian adalah siswi di boarding schoolarea urban di Kota Yogyakartadengan besar sampel 124 siswi. Pengambilan data menggunakan kuesioner praktik higiene menstruasi. Data dianalisis dengan teknik statistik deskriptif.Hasil: Secara umumpengetahuan dan praktik higiene menstruasi responden sudah baik. Hampir semua responden (98%) menjawab tepat pada pernyataanmenstruasi sebagai hal yang normal dan pernyataan dengan banyak jawaban yang salah adalah menstruasi sebagai tanda masuknya masa pubertas. Praktik higiene menstruasi yang paling seringdilakukan oleh responden mandi lebih dari satu kali sehari pada saat menstruasi(99,2%). Sementara untuk praktik higiene menstruasi yang masih kurang tepat yaitu arah membersihkan daerah kemaluan(45,2%).Kesimpulan: Responden memiliki pengetahuan yang tepat terkait pengetahuan higiene menstruasi. Bagi pengelola sekolah pada bidang bimbingan dan konseling dapat meningkatkan pengetahuan serta praktik higiene menstruasi terhadap aspek yang kurang tepat seperti hormon yang mempengaruhi menstruasi, periode menstruasi, frekuensi penggantian pembalut, pemilahan wadah dalam pembuangan pembalut, dan tempat menjemur celana dalam.